Dose-Ranging Study of Ceftriaxone for Uncomplicated Gonorrhea in Men - Handsfield, H. Hunter (1981)
Uncomplicated gonorrhea in men was successfully treated with ceftriaxone in single intramuscular doses of 125 mg (15 patients), 250 mg (16 patients), or 500 mg (15 patients). All 45 pretreatment gonococcal isolates tested were inhibited by ≤0.016 μg of ceftriaxone per ml. Treatment was well tolerated and caused no toxicity.